Implementation of a Perception Algorithm for a Mobile Robot Using ROS - SAIED, Boufateh Lahcen; HASSASA, Mohamed Badredinne; OUBBATI Brahim Khalil (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2022)
The purpose of this master project is to implement a perception algorithm for a Pioneer mobile robot using the ROS platform. The introductory segment of this memory report talks about the generalities of ROS, mobile robots, and the SLAM algorithm. Firstly, we use the Gmapping algorithm to build a 2-D map of an unknown environment and estimate the trajectory of the robot.Secondly, we tested experimentally another SLAM technique (RGB-D) using the Kinect sensor to build a 3-D map.The simulation and experimental results show that the implementation of the perception algorithms is better in terms of building 2-D and 3-D maps and navigation.
OPTION: Automation & Industrial Computing